TIGA PELOPOR BANGKITNYA NASIONALISME DI AWAL PERGERAKAN INDONESIA. BUDI UTOMO, SAREKAT ISLAM, DAN INDISCHE PARTIJ - Nurhaolillah; Syahril; Soraya Rasyid; Muhammad Fahmi (CARITA: Jurnal Sejarah dan Budaya, 2025)
This study examines three Indonesian national movement organizations : Budi Utomo, Sarekat Islam and Indische partij, which played pivotal roles in Indonesia’s struggle for independence. The research aims to analyze the background of their establishment, visions and missions and contributions to national awakening and the formation of Indonesian identitiy. This study employs a descriptive qualitative method with a literature review approach, utilizing historical sources such as books, scholarly articles and official documents. The findings reveal that Budi Utomo, focused on education and cultural development, SI emphasized empowering indigenous communities economically through trade, and Indische Partij advocated for cross-ethnic unity in resisting colonialism. These three organizations played complementary roles in laying the foundation of Indonesian nasionalism. The study underscores that despite their different approaches, a shared vision to end colonialism served as the commom thread in their struggles.